Human sexuality in physical and mental illnesses and disabilities - Sha'ked, Ami (Indiana University Press, 1978)
Contrary to common myths that portray the disabled person as sexless, there is accumulating clinical and research evidence suggesting that sexual interest and activity continue to be very important in the lives of many long-term patients and physically and mentally disabled persons. Furthermore, authorities assert that sexual adjustment is at the core of total medical and psychosocial rehabilitation of disabled patients. Consequently, health-care practitioners are confronted with increasing demands from disabled and chronically ill patients for counseling and advice in sexual matters.